Association Between Sedentary Behavior and Eating Habits According to Physical Activity Level in Brazilian Adolescents - De Moraes-Ferrari, G (LIPPINCOTT WILLIAMS & WILKINS, 2025)
IntroductionThe aim of this study was to investigate the association between sedentary behavior (SB) and eating habits of children and adolescents according to their physical activity (PA) levels.MethodA total of 1011 adolescents participated in the study, comprising 454 males and 557 females. Data were self-reported via pen-and-paper questionnaires completed in classrooms. The relationship between three SB domains (television (TV), computer, and cellphone) and eating habits according to PA level was analyzed using Pearson s correlation and linear regression. A cluster analysis was also conducted for high SB in the three domains.ResultsIn inactive adolescents, TV use (beta = 0.07, 95% confidence interval (CI) = 0.01-0.13, P = 0.04) and computer use (beta = 0.07, 95% CI = 0.01-0.12, P = 0.04) were associated with higher consumption of fried foods, whereas computer use (beta = 0.07, 95% CI = 0.01-0.13, P = 0.04) and cellphone use (beta = 0.07, 95% CI = 0.01-0.12, P = 0.04) were associated with consumption of sugary foods. Cellphone use was also associated with the consumption of soft drinks in inactive adolescents (beta = 0.05, 95% CI = 0.01-0.11, P = 0.00). In active adolescents, only TV use (beta = 0.16, 95% CI = 0.04-0.28, P = 0.00) and computer use (beta = 0.11, 95% CI = 0.01-0.21, P = 0.03) were associated with consumption of sugary foods. Together, the three domains of SB had an inverse relationship with vegetable consumption (beta = -0.08, 95% CI = -0.17 to -0.01, P = 0.00) and were positively related to the consumption of fried foods (beta = 0.08, 95% CI = 0.01-0.16, P = 0.02) and sugary foods (beta = 0.10, 95% CI = 0.02-0.18, P = 0.01) in inactive adolescents. Active adolescents only presented an increased consumption of sugary foods (beta = 0.15, 95% CI = 0.02-0.27, P = 0.02).ConclusionPhysically inactive adolescents display stronger associations between higher SB and poor eating habits, including an increased consumption of fried foods and sugary foods and a decreased consumption of vegetables.